Lived da'wah: Temporal structuring of religious practice in Tabligh jamaat's daily congregation - Busral, Busral; Rambe, Khairul Fadli; Gunawan, Rizky; Jaafar, Azhar; Habibi, Usman Arif; Engkizar, Engkizar (Jurnal Ilmu Dakwah, 2025)
Purpose - The main objective of this study is to understand the daily routine of Jemaah Tabligh deeply and to analyze how they integrate various aspects of da'wah (proselytizing) into their daily practices. Method - This research employs a qualitative method, specifically phenomenology, and the data source consists of individual in-depth interviews. All data were analyzed using the Miles and Huberman technique. Result - The analysis shows that the khuruj activities carried out by the Tabligh Jamaat group are divided into four daily routines: from early morning to morning, with seven activities; in the afternoon, with six activities; in the evening, with four activities; and at night, with six activities. This demonstrates that the Jamaah Tabligh group is a highly structured, disciplined, and organized entity in its missionary work. Implication – Based on studies of the Tabligh Jamaat movement, da'wah in the modern era can adopt several key strategies. First, it is important to establish consistent, structured routines, as demonstrated by the Tabligh Jamaat, to maintain the enthusiasm and commitment of members. Second, participatory learning methods such as halaqah should be intensified so that congregants can actively engage in discussions rather than merely passively receiving information. Third, focus on self-improvement (ishlah diri) and setting a good example (uswah hasanah), which are essential points, as da'wah must begin with oneself and be demonstrated through daily behavior. Fourth, the use of symbolic values through simple activities such as eating together can be an effective way to strengthen brotherhood and Islamic values. Originality/Value - The originality of this study lies in its in-depth analysis of Jemaah Tabligh's daily lifestyle and da'wah routines, which emulate the Prophet Muhammad's da'wah practices, providing a unique insight into the implementation of traditional da'wah in the modern era. *** Tujuan - Tujuan utama penelitian ini adalah untuk memahami rutinitas harian Jemaah Tabligh secara mendalam dan menganalisis bagaimana mereka mengintegrasikan berbagai aspek da'wah (penyebaran agama) ke dalam praktik harian mereka. Metode - Penelitian ini menggunakan metode kualitatif, khususnya fenomenologi, dan sumber data terdiri dari wawancara mendalam individu. Semua data dianalisis menggunakan teknik Miles dan Huberman. Hasil - Analisis menunjukkan bahwa aktivitas khuruj yang dilakukan oleh kelompok Tabligh Jamaat dibagi menjadi empat rutinitas harian: dari pagi buta hingga pagi hari, dengan tujuh aktivitas; siang hari, dengan enam aktivitas; sore hari, dengan empat aktivitas; dan malam hari, dengan enam aktivitas. Hal ini menunjukkan bahwa kelompok Jamaah Tabligh merupakan entitas yang sangat terstruktur, disiplin, dan terorganisir dalam pekerjaan misionarisnya. Implikasi – Berdasarkan studi tentang gerakan Tabligh Jamaat, dakwah di era modern dapat mengadopsi beberapa strategi kunci. Pertama, penting untuk menetapkan rutinitas yang konsisten dan terstruktur, seperti yang ditunjukkan oleh Tabligh Jamaat, untuk mempertahankan antusiasme dan komitmen anggota. Kedua, metode pembelajaran partisipatif seperti halaqah harus ditingkatkan agar jamaah dapat aktif berpartisipasi dalam diskusi daripada hanya menerima informasi secara pasif. Ketiga, fokus pada perbaikan diri (ishlah diri) dan memberikan teladan yang baik (uswah hasanah), yang merupakan poin penting, karena dakwah harus dimulai dari diri sendiri dan ditunjukkan melalui perilaku sehari-hari. Keempat, penggunaan nilai-nilai simbolis melalui aktivitas sederhana seperti makan bersama dapat menjadi cara efektif untuk memperkuat persaudaraan dan nilai-nilai Islam. Orisinalitas/Nilai - Keaslian studi ini terletak pada analisis mendalamnya terhadap gaya hidup sehari-hari dan rutinitas da'wah Jemaah Tabligh, yang meniru praktik da'wah Nabi Muhammad, memberikan wawasan unik tentang implementasi da'wah tradisional di era modern.